A study of the strength of soft clay in reinforced with group encapsulated bottom ash columns - Nur Aqilah, Muhd Drus (2015)
The increasing of the demand and restrictions on the suitable land for construction in recent time led the construction industries to exploit sites that were previously considered as the uneconomical site to develop such as soft clay soil. Luckily, the advance of the technology prove that there is an alternative to using soft clay in construction by ground improvement or modification technique. The ground improvement method are increasing the shear strength, reduces the permeability and the compressibility of the soft soil. The stone column method is the most preferable and widely used in construction. This study are used the waste materials known as bottom ash as a replacement to the usage of natural materials in the stone column. Hence, by reutilize the waste of bottom ash, the construction cost can be reduce and thus, the disposal area also decreasing. This research is to determine the strength of the soft clay in reinforced with group encapsulated bottom ash columns. The bottom ash in encapsulated with geotextile are used as the stone column in kaolin clay. At the first part of the study, the physical and mechanical properties of the kaolin clay and bottom ash are determine. There is proven that the kaolin clay can be classified as silty soils while, the bottom ash have the relative characteristic with granular materials. At the second part of study, the sample of soft clay in reinforced with group of three encapsulated bottom ash columns are tested under Unconsolidated Undrained Test with difference various of diameter and height of bottom ash column. It can be concluded that the presence of encapsulated bottom ash column, are increasing the shear strength parameter of the soft clay.